Legal Protection Against Abortionists Of Rape Victims - Susi Delmiati (Faculty of Law, Universitas Pekalongan, 2023)
Rape is a crime that causes trauma to the victim, besides the trauma of rape can also cause pregnancy in the victim. Pregnancy from rape behavior is certainly a pregnancy that the victim did not expect, so that not a few have abortions for their pregnancies. This study aims to determine the legal protection for abortion perpetrators who are rape victims. This study uses a normative legal research method with a normative juridical approach, while data collection techniques are carried out by exploring journals, books and applicable laws and regulations. The results of the study show that legal protection for abortion victims of rape is with the policy of Article 76 of the Health Law which considers the condition of rape victims so as to allow abortion with certain conditions stated in the law in it.